2015
DOI: 10.3389/fimmu.2015.00299
|View full text |Cite|
|
Sign up to set email alerts
|

Defining Mononuclear Phagocyte Subset Homology Across Several Distant Warm-Blooded Vertebrates Through Comparative Transcriptomics

Abstract: Mononuclear phagocytes are organized in a complex system of ontogenetically and functionally distinct subsets, that has been best described in mouse and to some extent in human. Identification of homologous mononuclear phagocyte subsets in other vertebrate species of biomedical, economic, and environmental interest is needed to improve our knowledge in physiologic and physio-pathologic processes, and to design intervention strategies against a variety of diseases, including zoonotic infections. We developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 86 publications
11
78
0
Order By: Relevance
“…The BAL cells were then sorted by flow cytometry and the transcriptomic expressions of 10 genes previously identified as differentially expressed in these populations by us [2, 14] and others [4, 15, 16] were measured by RT-qPCR (Fig 2A). In order to easily compare those results with those we previously obtained, we depicted previously published data from parenchymal cells [2] as closed symbols in Fig 2A and as the “PAR” columns in the heat map (Fig 2B) we designed to summarize the RT-qPCR data.…”
Section: Resultsmentioning
confidence: 99%
“…The BAL cells were then sorted by flow cytometry and the transcriptomic expressions of 10 genes previously identified as differentially expressed in these populations by us [2, 14] and others [4, 15, 16] were measured by RT-qPCR (Fig 2A). In order to easily compare those results with those we previously obtained, we depicted previously published data from parenchymal cells [2] as closed symbols in Fig 2A and as the “PAR” columns in the heat map (Fig 2B) we designed to summarize the RT-qPCR data.…”
Section: Resultsmentioning
confidence: 99%
“…That these subpopulations of cDC share a common genetic signature has been reported previously in sheep, mouse and human243350556465. A recent study confirmed orthology between the blood cDC1 population in pig with mouse and human equivalents, although the authors were unable to make any claims on the cDC2 population56. In this study, cDC1 were identified based on CADM1 expression27 rather than an absence of CD1 expression as employed here.…”
Section: Discussionmentioning
confidence: 49%
“…To explore a broader range of DC markers, we compared the porcine DC populations at the transcriptome level. This also enabled us to determine if the DC populations share a common gene expression signature as has been recently described for other species2433505556. Employing a custom made NimbleGen 12 × 135 K porcine array spanning a total of 19,351 genes, we investigated the gene expression profile of the FACS sorted CD1 − , CD1 + and pDC populations from three separate pigs and compared these with monocytes from the same pigs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the pattern of CD11c expression on pig skin and blood myeloid cell subsets whose organization aligns across species (4143), is closer to the human than to the mouse one, making pig a pertinent preclinical model to evaluate this type of targeting. Indeed, CD11c shows a higher expression on cDC2 than on cDC1 and is highly expressed on skin monocyte-derived cells in the pig and human (25, 44) and not in the mouse (45).…”
Section: Discussionmentioning
confidence: 99%